Geo-Information enabled crime predictive analysis model - Ritvik Chauhan; Vijay Kumar Baraik (National Geographical Journal of India, 2022)
Crime is a serious threat to society and handicaps it in its normal functioning with full potential. It also hinders the development of a society along with creating hurts of various kinds and degrees. It is, therefore, required to tackle the crime properly for its control and management. Associated with human society with its very existence, it has been evolving with the time in differing magnitudes. Especially, during the contemporary time of rapid technological and societal change, crime has got new types, forms spatial scale with the advent of globalization since 1990. However, the spatial studies on crimes are recent ones despite place plays an important role in understanding and tackling crimes. The sophisticated geospatial tools like Remote Sensing, Geographical Information System and GPS have provided vast scope to map and study crime in relation to space and other aspects of crime. This study focuses on the crime mapping for the years 2001, 2006, and 2012 covering aspects of crimes like changing patterns and trends, seasonality-diurnality, and zonation maps with identification of hotspots using the latest tools of mapping. It also attempts to work on a spatially enabled Predictive Analysis Model using various characteristics and associations. It is expected to provide a base for highlighting the importance of geographical factors in crime analysis, prediction and management for an intelligence system for the past, present and future. This study has utilized both primary as well as secondary data for the geographical analysis in assessing crime pattern in the area of study.